RESTRUKTURISASI KREDIT DAN KEBERLANGSUNGAN USAHA UMKM DIMASA PANDEMI COVID-19 ( STUDI PADA BANK BTPN SYARIAH CABANG PURWOREJO KLAMPOK) - Cahyaningrum, Tyas; Rudianti, Walid; Ainiyah, Ghonimah Zumroatun; Yubiharto, Yubiharto (Medikonis, 2024)
ABSTRACT The Covid-19 pandemic that occurred has had a huge impact on customers in the MSME sector. The implementation of large-scale social restrictions forced people to stay at home, this greatly affected the business activities carried out by MSME players, where there was a decrease in turnover which also affected MSME credit. The aim of this research is to determine the process of implementing credit restructuring and business continuity during the Covid-19 pandemic. This research was conducted at Bank BTPN Syariah Purworejo Klampok branch using qualitative research methods. The data source is primary data. The primary data source in this research was obtained directly through interviews. The informants for this research are Btpn Syariah Customers and Employees. Data collection used observation and interview methods. Data analysis techniques use data reduction, data display, and data verification. The results of this research show that credit restructuring as credit anticipation due to Covid-19 according to Indonesian laws and regulations has been implemented effectively. Credit restructuring can save creditors from bad credit, debtors have the opportunity to organize their business and finances and then have the ability to repay their deb.